SECURITY: Behind the Visible - Muhamad Fathur Rizki; Irwan Sarbeni (Cinematology: Journal Anthology of Film and Television Studies, 2022)
This research was motivated by the outpouring of the security guards at the Andes Cluster security post, which is where the researcher lives. many things are discussed by the security guards including the existence of one eye on the security guard profession and their salaries are not worth the risk. This one eye view also makes it seem as if the security guard profession is a lowly profession compared to others, such as the police or other security forces. So, it can be formulated in this research that how the security guard is underestimated by many people and how is the security guard's welfare. The purpose of this study was to determine the true view of the security guard profession and to determine the welfare of security guards with high job risks. The research method used in this study is a qualitative method with an analytical descriptive approach. That is, an approach that analyzes, describes and summarizes various conditions, situations from various data from interviews or observations about problems directly in the field. From interviews and observations made, it was explained that their salary was very small, only 1.6 million rupiah. Meanwhile, the views of the residents themselves on their profession are not all looked down on. Indeed, we should not look down on the security guard profession. Even though they seemed to be just relaxing, the responsibility they received was heavy. The issue of a salary increase is not easy, because the security guard can't do anything. It is the foundation, the developer and the residents who can make the security guard's salary increase.